(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2025)
This article considers the urgent issue of developing professional, ethical and cultural relations in students of pedagogical specialties who are future teachers. The authors emphasize that the development of teachers as individuals capable not only of imparting knowledge, but also of instilling in their students moral values and respect for cultural diversity directly depends on the quality of their moral and cultural preparation. The article analyzes the main components of moral relations, such as responsibility, honesty, justice and respect for each student, as well as cultural relations such as tolerance, intercultural competence and appreciation of cultural heritage. It considers the impact of these relations on teaching, creating a favorable educational environment and developing a civic position in the younger generation.